1988
DOI: 10.1002/ptr.2650020404
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological actions of the gut active principles in Croton penduliflorus hutch. Seed on isolated smooth and skeletal muscles and on blood pressure

Abstract: The effects of Croton penduliporus seed crystals (CP crystals) were investigated on isolated guinea-pig ileum, chick biventer cervicis muscle and frog rectus abdominis muscle. The effect of the crystals on blood pressure of normotensive Sprague Dawley rats was also investigated. CP crystals induced concentrationsdependent contractions in the guinea-pig ileum with ECS0 of 2.29 X g/mL. Contractions induced by CP crystals in the guinea-pig ileum were not inhibited by atropine (2 X 10-7-l.2 X g/mL), tetrodotoxin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It forms a major component of herbal contraceptives, abortifacient and anti-fibroid concoctions used in the local treatment of fibroids (Adjanohoun et al, 1996;Odesanmi et al, 2006). Asuzu and Chineme (1987), Asuzu et al (1988Asuzu et al ( , 1989 indicated that Croton penduliflorus seed oil had irritant effect on the gastrointestinal tract and induced adverse effects on the internal organs including liver and kidneys and central nervous system of mice. It also induced pharmacological effects on isolated smooth and skeletal muscles and blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It forms a major component of herbal contraceptives, abortifacient and anti-fibroid concoctions used in the local treatment of fibroids (Adjanohoun et al, 1996;Odesanmi et al, 2006). Asuzu and Chineme (1987), Asuzu et al (1988Asuzu et al ( , 1989 indicated that Croton penduliflorus seed oil had irritant effect on the gastrointestinal tract and induced adverse effects on the internal organs including liver and kidneys and central nervous system of mice. It also induced pharmacological effects on isolated smooth and skeletal muscles and blood pressure.…”
Section: Introductionmentioning
confidence: 99%